Pendampingan UMKM Desa Leces melalui Penerapan Google Maps sebagai Media Promosi Digital - Devy Habibi Muhammad; Alda Eky Nur Kholifah; Rina; Ahmad Paeng; Siti Khomsah Apsari (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This community service program was carried out in Leces Village with the aim of digitizing micro, small, and medium enterprises (MSMEs) through the utilization of Google Maps as a promotional and marketing tool. The method applied was Participatory Action Research (PAR), involving active participation of the community in each stage, including preparation, implementation, and evaluation. The program involved 10 MSMEs from two hamlets, mostly engaged in food businesses, small grocery stores, and batik handicrafts. The results indicate that all MSMEs were successfully registered on Google Maps, making their businesses digitally accessible to a wider audience. Nevertheless, several challenges were identified, such as limited digital literacy, difficulties in independently managing Google Maps accounts, and technical barriers like unstable internet connectivity. Despite these constraints, the evaluation revealed positive impacts, including increased community awareness of digital promotion and new customers for several MSMEs after being registered on Google Maps. Therefore, this program has proven effective in enhancing basic digital literacy and expanding market access for MSMEs in Leces Village, although continuous assistance is needed to ensure program sustainability.